Effect of time and ultrasonic activation on ethylenediaminetetraacetic acid on smear layer removal of the root canal - de Castro, Fábio Pereira Linhares; Pinheiro, Sérgio Luiz; Duarte, Marco Antônio Húngaro; Duque, Jussaro Alves; Fernandes, Samuel Lucas; Anchieta, Rodolfo Bruniera [UNESP]; da Silveira Bueno, Carlos Eduardo (Wiley, 2016)
The aim of this study was to assess the effect of time and the ultrasonic activation of ethylenediaminetetraacetic acid (EDTA) in removing the smear layer of at root canal. A total of 60 bovine inferior incisors were transversely sectioned and instrumented; A smear layer was added in the root dentin surface. The specimen were then divided into six groups according to the following final irrigation protocols: Group (G) 1: conventional irrigation with sodium hypochlorite (NaOCl); G2: conventional irrigation with NaOCl + EDTA for 20 s; G3: conventional irrigation with NaOCl + EDTA for 60 s; G4: passive ultrasonic irrigation (PUI) with NaOCl; G5: PUI with NaOCl + PUI with EDTA for 20 s; G6: PUI + NaOCl and PUI with EDTA for 60 s. Samples were analyzed by scanning electron microscope (SEM) at ×500 increase. The images were measured by three blinded evaluators and classified in scores ranging from 1 to 5. The results were analyzed by the Pearson correlation test and the ANOVA nonparametric Kruskal–Wallis and Dunn's tests were used for the comparisons. Irrigated samples only with NaOCl (G1 and G4) had higher scores when compared with other groups. G5 and G6, irrigated with 17% EDTA and ultrasonic irrigation had lower scores. However, there was no statistically significant difference in G2 and G3, where there was no irrigation. It was concluded that irrigation with 17% EDTA for 20 s promoted the effective removal of smear layer, regardless of ultrasonic irrigation.
Keywords: dentin; EDTA; scanning electron microscopy; smear layer